1992
DOI: 10.1177/00220345920710090501
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Human Salivary Proteins to Hydroxyapatite: A Comparison Between Whole Saliva and Glandular Salivary Secretions

Abstract: The protein compositions of in vitro pellicles formed from whole saliva and parotid and submandibular secretions were determined by use of synthetic hydroxyapatite as a model for dental enamel. The adsorbed and unadsorbed protein fractions were analyzed by amino acid analysis and both anionic and cationic discontinuous polyacrylamide gel electrophoresis. For further characterization of the in vitro pellicle, the adsorbed fractions were subjected to gel filtration on Sephadex G-100 and reversed-phase chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 27 publications
1
112
0
8
Order By: Relevance
“…On hydrophilic silica surfaces the steep slopes of the isotherms and the high adsorbed amounts of the investigated proteins (correlating to side-on and end-on monolayer at concentrations relevant in saliva) suggests that these proteins have strong driving forces for adsorption, comparable to those observed for salivary secretions [14,33,34,38] and single key-pellicle proteins [41,48].…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…On hydrophilic silica surfaces the steep slopes of the isotherms and the high adsorbed amounts of the investigated proteins (correlating to side-on and end-on monolayer at concentrations relevant in saliva) suggests that these proteins have strong driving forces for adsorption, comparable to those observed for salivary secretions [14,33,34,38] and single key-pellicle proteins [41,48].…”
Section: Significancementioning
confidence: 86%
“…In vitro studies have shown that the candidacidal activity of histatin 5 is impaired when adsorbed to surfaces [10,11], but upon desorption it is reactivated. Histatins have been identified in both in vitro and in vivo formed pellicles [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The salivary cystatins, however, have not been shown to strongly antagonize Cathepsin B [62], and instead have been hypothesized to function in salivary glands as inhibitors of harmful proteinases expressed by pathogens [63]. Additionally, the salivary cystatins have been suggested to have high affinity for hydroxyapatite, the main mineralized component of bone tissue [64]. Thus, whether salivary cystatin production functions in bone metastasis via facilitating evasion of the immune system, or homing to the bone tissue, or by a different mechanism altogether, remains to be determined.…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…Statherin efficiently hinders the crystallization of hydroxyapatite in the supersaturated environment of saliva [68][69][70][71][72][73]. The statherins have historically served as one of the best characterized models for understanding the functional activities of proteins in the physicalchemical control of hydroxyapatite growth.…”
Section: Statherin: a Protein That Regulates Crystallization Of Hydromentioning
confidence: 99%